Restricción de la distribución de Mesoclemmys vanderhaegei (Bour, 1973) (Testudines: Chelidae) en Argentina - Cassano, María Julia (2016)
The presence of the chelid turtle Mesoclemmys vanderhaegei in Argentina is currently restricted to some localities in Misiones, Corrientes and Formosa provinces. The only record for the last province was based in two specimens originally referred as M. vanderhaegei from the “Reserva Ecológica El Bagual”, which have been considered lost from the herpetological collection of the reserve. In a revision of the turtles at the herpetological collection of the Museo de La Plata both specimens were found. Both specimens, male and female, bear hypertrophied tubercles on the posterior face of the thigh, supporting that they actually correspond to Acanthochelys pallidipectoris. Thus, at the light of present evidence, the distribution of M. vanderhaegei in Argentina should be restricted to a small area at northern Corrientes and southern Misiones provinces.